2022
DOI: 10.18280/ria.360408
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Academic Performance of Students with Hearing Impairment

Abstract: Around 5 million people in India are with hearing impairment. The higher education opportunities for students with hearing impairment are very limited. Only six institutes in the country provide undergraduate degrees to students with hearing impairment, according to accessible records. Academic achievement in the past, student background characteristics, and eLearning elements are all aspects that influence a student's academic performance. Hearing impairment-related characteristics may also need to be conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The pilot study of this research [29] revealed that deafnessrelated factors have a strong contribution to the academic performance of students with hearing loss. According to a thorough study done in Saudi Arabia using data of DHH students, there is a strong correlation between student grades, demographics, geographic region, school, course type, and course score when predicting academic outcomes.…”
Section: Related Workmentioning
confidence: 85%
See 1 more Smart Citation
“…The pilot study of this research [29] revealed that deafnessrelated factors have a strong contribution to the academic performance of students with hearing loss. According to a thorough study done in Saudi Arabia using data of DHH students, there is a strong correlation between student grades, demographics, geographic region, school, course type, and course score when predicting academic outcomes.…”
Section: Related Workmentioning
confidence: 85%
“…The collected data needs to be refined in the following ways (i) data cleaning (ii) data discretization (iii) feature encoding and (vi) Feature scaling were used in the preprocessing stage [29] as shown in Figure 3.…”
Section: Data Preprocessingmentioning
confidence: 99%